L'appropriation d'une innovation par ses usagers : autour du futur Learning centre de l'Université de Haute Alsace - Bernard Coulibaly; Hélène Hermann
This article presents the results of a research on the relationship students and teachers have with documentary resources as far as learning, pedagogy and the use of ICT are concerned. The purpose of the inquiry is to explore and offer suggestions on the conditions which could encourage the users to resort to the Learning Centre that the University of Haute Alsace plans to open in 2017. It examines the work habits and the use of documentary collection of both students and teachers as well as their expectations regarding an ideal university library. Results show that both students and teachers rarely visit the university libraries. The students strongly expect improvements regarding the physical, spatial and technological environment together with the quality and especially the congenial aspect of the university libraries. For their part, the teachers want a wide range of digital resources at their disposal. These results have led us to make suggestions that should support appropriation of the innovation brought about with implementing a Learning Centre.